Rural Agricultural Development and Farmer Empowerment in North Lombok Within The National Policy Framewor - Zainab Zainab; Baharuddin Baharuddin; Jalaluddin Jalaluddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Agricultural and rural development policies in Indonesia are strategically designed to promote food security, reduce rural poverty, and empower farmers. However, persistent gaps between national policy objectives and local implementation remain evident, particularly in peripheral and island regions such as North Lombok Regency, West Nusa Tenggara. This study aims to critically review agricultural and rural development policies in Indonesia by focusing on farmer empowerment within the framework of national policy implementation at the local level. This article employs a qualitative literature review method by systematically analyzing peer-reviewed journal articles, policy documents, and relevant reports published over the last decade. The review emphasizes theoretical perspectives on participatory rural development, the capability approach, and place-based policy to interpret policy dynamics and implementation outcomes. The results indicate that agricultural and rural development policies are largely normative and production-oriented, with limited adaptation to local socio-economic and agro-ecological contexts. Weak institutional capacity, fragmented policy coordination, and insufficient farmer participation have constrained the effectiveness of empowerment initiatives in North Lombok. The findings further highlight that farmer empowerment is more strongly influenced by institutional support and governance quality than by individual farmer characteristics alone. In conclusion, effective agricultural and rural development requires a contextual, participatory, and institutionally grounded policy approach. Strengthening local institutions, enhancing policy convergence across sectors, and adopting place-based development strategies are essential to improving farmer empowerment and rural economic resilience. It is recommended that future policies prioritize institutional strengthening and locally adaptive frameworks to ensure inclusive and sustainable agricultural and rural development.